PEMBINAAN MOTIVASI BELAJAR SISWA DITINJAU DARI PSIKOLOGI ISLAM - Sri Hartati; Rahmawati Wae (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2019)
This study intends to look at a study of the business and activities that have been carried out in order to foster motivation to learn in one MAN in the city of Padang. The main problem is how the implementation of student learning motivation and programs that have been carried out by the school in the school is viewed from the viewpoint of Islamic Psychology. This research pattern field research with descriptive methods based on observation and interviews. Sources of data from this study consist of primary data and secondary data. Primary data are written and unwritten information from schools, principals, teacher and student assemblies. While the secondary data are information materials from other parties that have something to do with the problem under study. The results of the study showed that the school had designed and implemented a program that was conducted structured in giving motivation to learn to improve students' achievement through two channels, namely extra and intra-curricular. Extra-curricular activities in the fields of arts, sports and languages. To students who excel will be given awards in the form of scholarships, prizes and others. Whereas through the intra-curricular pathway, among others, the implementation of a good teaching and learning process and the placement of teaching staff in accordance with their respective fields of expertise and competence, so that there are no teachers who teach outside their fields of expertise. In addition, good cooperation has been carried out between leaders, student council advisers and counselors with intra-school organizations (OSIS). Keywords: Development, Learning Motivation, Islamic Psychology